The relationship between locus of control and inventory of attitude toward seeking professional psychological help scale at Nielsen Company (Eastern Region) Kota Bharu, Kelantan / Fatin Farhanah Haji Omar - Haji Omar, Fatin Farhanah (2014)
A locus of control is a person's belief about how much power one has over the events in one's life. The locus of control is a dimension of personality, it helps explain one's traits and behavior. A large scale study was conducted to identify the influencing factors of inventory attitudes (psychological openness, help seeking propensity, indifference to stigma) and certain demographic variable towards seeking professional psychological help to the locus of control. There were 362 female nurses with diploma education were enroll in this study. The data were analyzed by Binary Logistic Regression using enter method and backward elimination method. Finally, this study was found that the variable religion and indifferent to stigma are significant for both methods